Evaluation of maternal admission to intensive care unit in a tertiary care hospital of Kashmir valley - Rashid, Rehana; Galzie, Saniyah Khan; Ahmed, Javid (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Management of critically ill obstetric women at an ICU is a challenge to both physicians and obstetricians due to physiological adaptations and progress of diseases during pregnancy and puerperium. There has been a striking association between the number of maternal deaths and the accessibility to ICU care. Obstetric patients get admitted to the ICU approximately at 0.1-0.9% times of all deliveries. Objective was to evaluate the occurrence, indication and outcome of patients admitted in the ICU of an obstetric tertiary care hospital. Methods: This retrospective study was carried out from August 2020 to January 2021 at Lalla Ded Hospital, a tertiary care Obstetrics and Gynaecology Hospital of Kashmir valley. Data for this study was collected retrospectively from hospital records. The demographic details, indication for ICU admission, co-morbidities, ante natal care records were noted on admission to the ICU. Results: The total ICU admission during this time period was 212 (1.44%) with obstetric patients being 194 (91.5%) and gynaecologic patients 18 (8.5%). Obstetric haemorrhage (38.2) followed by hypertensive disorders of pregnancy (24.1%) were the most common indications for ICU admission. 26.9% patients needed mechanical ventilation during ICU admission. Conclusions: Analysing intensive care unit utilization during pregnancy can be an accepted approach to identify severe and near miss maternal morbidity. Development and upliftment of primary health care facilities with involvement of multi-disciplinary teams and referral of high risk pregnancies to higher health centres is the key to decrease maternal mortality and morbidity.